TINJAUAN HUKUM PEMBENTUKAN BADAN USAHA MILIK DESA (BUMDES) DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Tobi Ricardo (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTLaw Number 6 of 2014 concerning Villages raises hope for the progress of the Village to increase its role in the economic system. Village-Owned Enterprises are regulated in CHAPTER X Article 87 paragraph 1 of Law Number 6 of 2014 concerning Villages, stating "Villages can establish Village-Owned Enterprises called BUMDes". In the Formation of Village-Owned Enterprises in Indonesia, there are still many villages that have not been able to form and do not understand how to establish Village-Owned Enterprises that have been mandated by the Village Law.The problem raised in this paper is how the process of forming a Village-Owned Enterprise is and what factors cause failure in the formation of a Village-Owned Enterprise. The type of research used is normative juridical research, based on researching library materials or secondary data consisting of primary legal materials, secondary legal materials and non-legal materials.The results showed that the process of forming a village-owned enterprise was carried out with the Village Deliberation to determine the name of the village-owned enterprise, select the board of directors, design and establish village regulations and articles of association, then register the village-owned enterprise at the ministry that carries out government affairs in the legal field. and human rights to obtain a legal entity certificate. Factors that cause failure in the formation of Village-Owned Enterprises are forming village-owned enterprises by trial and error without proper study, determining or choosing which business to run even though they do not master the chosen business, ending up giving up and being afraid to repeat, weak human resources and the limited basic infrastructure of a village.